Advancing workforce diversity by leveraging the Clinical and Translational Science Awards (CTSA) program. Issue 1 (9th November 2023) - Locklear, Tracie; Lewis, Roslyn; Calhoun, Faye; Li, Andy; Dickerson, Kathryn C.; McMillan, Amanda; Davis, Lisa; Dzirasa, Kafui; Weinfurt, Kevin P.; Grambow, Steven C.
Abstract: Clinical trials continue to disproportionately underrepresent people of color. Increasing representation of diverse backgrounds among clinical research personnel has the potential to yield greater representation in clinical trials and more efficacious medical interventions by addressing medical mistrust. In 2019, North Carolina Central University (NCCU), a Historically Black College and University with a more than 80% underrepresented student population, established the Clinical Research Sciences Program with support from the Clinical and Translational Science Awards (CTSA) program at neighboring Duke University. This program was designed to increase exposure of students from diverse educational, racial, and ethnic backgrounds to the field of clinical research, with a special focus on health equity education. In the first year, the program graduated 11 students from the two-semester certificate program, eight of whom now hold positions as clinical research professionals. This article describes how leveraging the CTSA program helped NCCU build a framework for producing a highly trained, competent, and diverse workforce in clinical research responsive to the call for increased diversity in clinical trial participation.